Problemy zdrowotne polskich emigrantów poakcesyjnych. Implikacje dla systemów opieki zdrowotnej - Agata Smoleń (Problemy Zarządzania, 2013)
Economic migration entails a higher health risk, due to types of work performed by immigrants, their living conditions and lifestyle changes. The increased health risk concerns especially infectious diseases (including sexually-transmitted diseases), accidents and injuries, musculoskeletal system diseases and psychoactive substances abuse. Migrants are also more prone to mental health conditions such as stress, depression and adjustment problems. Studies indicate that many immigrants do not use health care in the host country even though they are eligible for publicly funded health services and have health needs.